Does neuroinflammation turn on the flame in Alzheimer's disease? Focus on astrocytes - Steardo, Luca; Bronzuoli, Maria R.; Iacomino, Aniello; Esposito, Giuseppe; Steardo, Luca; Scuderi, Caterina (Frontiers in Neuroscience, 2015)
Data from animal models and Alzheimer’s disease (AD) subjects provide clear evidence for an activation of inflammatory pathways during the pathogenetic course of such illness. Biochemical and neuropathological studies highlighted an important cause/effect relationship between inflammation and AD progression, revealing a wide range of genetic, cellular, and molecular changes associated with the pathology. In this context, glial cells have been proved to exert a crucial role. These cells, in fact, undergo important morphological and functional changes and are now considered to be involved in the onset and progression of AD. In particular, astrocytes respond quickly to pathology with changes that have been increasingly recognized as a continuum, with potentially beneficial and/or negative consequences. Although it is now clear that activated astrocytes trigger the neuroinflammatory process, however, the precise mechanisms have not been completely elucidated. Neuroinflammation is certainly a multi-faceted and complex phenomenon and, especially in the early stages, exerts a reparative intent. However, for reasons not yet all well known, this process goes beyond the physiologic control and contributes to the exacerbation of the damage. Here we scrutinize some evidence supporting the role of astrocytes in the neuroinflammatory process and the possibility that these cells could be considered a promising target for future AD therapies.